Mathematical modelling of golden apple drying and performance evaluation of solar drying systems using energy and exergy approach - Halefom Kidane; Istvan Farkas; Janos Buzás (Scientific Reports)
Abstract The study presents the energy and exergy analysis of two differently shaped dryers connected to the two same type of drying system and drying kinetics of the apple slice dried in the stated drying chambers. The exergy inflow, outflow and efficiency of the solar air hears and drying chamber were evaluated. The result revealed that significant variations in energy and exergy efficiencies were observed within the dryers and solar air heaters (SAHs). The average efficiency of SAH 1 and SAH 2 on day 1 were 53.85% and 49.79%, respectively, while the corresponding dryers’ average efficiencies were 37.94% and 36.15%. On day 2, the average efficiency of SAH 1 and SAH 2 were 47.18% and 44.19%, respectively, with the dryers’ average efficiencies of 35.9% and 34.4%. The average exergy efficiency followed the same pattern as energy efficiency, with SAH 1 and Dryer 1 being higher than SAH 2 and Dryer 2 on both days. The drying of apple slices took place entirely during the falling rate period. To predict drying behavior of the apple slices, ten thin-layer drying models were assessed. The Midilli et al. was found the best fit (R2 = 0.9969), followed by Logarithmic and Two-term models.